The Chaos becomes Discrete , through the STPL Mechanism , which is the Energy–Space Generator - Georgallides, Markos (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Everything in this cosmos , is Done or Becomes , from a Mould . Geometry has the Monad , a discrete continuity AB , Becoming from the Zero-Point ≡ 0 , and Mechanics-Physics the Recent-Acquisition of The Material-Geometry , where Zero-point 0 =  = ⊕+⊝ = The Material-point = The Quantum = Positive Space and Negative Anti-Space . [58] Monad in Geometry → Linearly is , through mould of Parallel Theorem [44-45] ,which are the equal distances between points of parallel and line → In Plane is through mould of Squaring the circle [46-47] , where the two equal and perpendicular monads consist a Plane acquiring the common Plane- meter ,π, → In Space (volume) is through mould of the Duplication of the Cube [44-46] , where any two Unequal perpendicular monads acquire the common Space-meter ,³√2 , to be twice each other . Monad in Mechanics and Physics is → The Material-point = discrete continuity |⊕+⊝|= The Quantum through mould of Space – Anti-space in itself , which is the material dipole in inner monad Structure and is Identical with the Electromagnetic cycloidal field of Energy monads .This is ,the distance , the deep concept of Material-geometry. Energy monads presuppose Energy-Space Base (the beyond Planck`s length ,Gravity`s and Spaces` levels ) the [PNS] Space Anti-Space as work → W = ∫ P.ds = 0 , which is the cause of Spaces existence and the motion of particles . Since these also are Quantized as the Complex numbers , then , this property is encountered in Stationary waves where energy E , is proportional to angular velocity w . This property of particles , Angular momentum = Spin , becomes from the Intrinsic , Inward , cycloidal wave motion, which is their cause of external motion as outward waves .The varying lever arms ,on cycloid-evolute is the cause of vibrations and which cause the EM-waves and Spin . Common-circle of radius , rc , is the common source of vibration excitation for the Space , Anti –space , considered as rotating with angular velocity ,w, and then their relative motion becomes the , Rolling of Space ABC on Anti-space AEBECE and since also this relative motion is applied on STPL [Six Triple Points Line] Mechanism , then DA ,PA , points on it are the corresponding linear links of vibrations and Poles of rotation . [STPL] is a Geometrical Mechanism that produces and composite all opposite Space and Anti-space Points to Material-points → Waves ← the three Breakages [s² = ± (w̅.r)² , [i] = 2(wr)²] of [MFMF] mechanism under v̅ = c̅ thrust , and through it are becoming The Fermions → [ ±